A comprehensive review of flexible alternating current transmission system (FACTS): Topologies,applications, optimal placement, and innovative models - Mehrdad Tarafdar Hagh; Mohammad Ali Jabbary Borhany; Kamran Taghizad-Tavana; Morteza Zare Oskouei (Heliyon)
This paper is a comprehensive reference for researchers interested in flexible AC alternating current transmission systems (FACTS) technologies. This study investigates modified UPFC models. Besides UPFC, an overview of DPFC will be presented, and the critical differences between these advanced power flow control technologies will be discussed. In particular, we will do a comparative evaluation of three well-known DPFC models: Distributed Series Reactor (DSR), Distributed Static Series Compensator (DSSC), and Distributed Unified Power Flow Controller (DUPFC). This work also discusses the latest models of FACTS technology, such as Carbon Nanotubes (CNT), Multi-winding transformers (MWT), and Line-to-Line Compensators (LLC). Finally, this review paper introduces advanced optimization techniques for optimal placement and design of FACTS devices.